The legacy of coercive cotton cultivation in colonial Mozambique - Henrique Barros; Rute Martins Caeiro; Sam Jones; Patricia Justino (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
We examine the long-term impact of forced labour on individual risk behaviour and economic decisions. For that, we focus on a policy of coercive cotton cultivation enforced in colonial Mozambique between 1926 and 1961. We combine archival sources about the boundaries of historical cotton concessions with survey data collected specifically for this study. By employing a regression discontinuity design to compare individuals living in areas inside and outside the historical cotton concessions, we document significant disparities in risk aversion and agricultural patterns between communities. Our findings reveal that individuals living in regions unsuitable for producing cotton but still subjected to the coercive cotton regime have higher risk aversion, are more likely to be farmers, and have more agricultural production destined to be commercialized. These results are mostly driven by women, who felt the brunt of the forced labour regime. As a novel contribution, this paper highlights the long-lasting consequences of colonial agricultural policies on risk and economic behaviour, offering insights into the challenges faced by post-colonial societies in overcoming historical legacies.
Keywords: F54; O13; D10; D81; 330; long-run development; colonialism; economic behaviour; regression discontinuity; Africa